Voltage drop apportionment in Eskom's distribution networks - Carter-Brown, Clinton Geoffrey (Department of Electrical Engineering, 2014)
Includes bibliographical references. Keywords: voltage drop Keywords: voltage apportionment Keywords: voltage control